Localization of the structural gene for threonine dehydrogenase in Escherichia coli. - Ravnikar, P D (1986)
The threonine dehydrogenase (tdh) gene of Escherichia coli, cloned within the plasmid pDR121, was inactivated in vitro by inserting a segment of DNA carrying the chloramphenicol acetyltransferase (cat) gene. The insertionally inactivated tdh gene was then transferred by homologous recombination into the E. coli chromosome by the procedure of Winans et al. (J. Bacteriol. 161:1219-1221, 1985). Mating experiments, followed by P1-mediated two- and three-point crosses, enabled us to localize tdh near min 81.2. The order with respect to known markers is mtl-cysE-tdh-pyrE.